Smaller distance between nest contents and cavity entrance increases risk of ectoparasitism in cavity‐nesting birds. (22nd July 2020) - Tomás, Gustavo; Ruiz‐Castellano, Cristina; Ruiz‐Rodríguez, Magdalena; Soler, Juan J.
Abstract : Determining costs associated with nest‐building behaviour and nest characteristics is of prime importance to understand the evolution of such extended phenotypic traits. We explored a cost of nest building experimentally to determine whether large nests attracted more ectoparasites. This cost may be especially important to cavity‐nesting species where larger nests likely reduce the distance between nest contents and the cavity entrance, making the host nest more vulnerable to ectoparasite detection. We manipulated the amount of nest material and the distance between nest and cavity entrance and estimated the abundance of ectoparasites ( Carnus hemapterus flies) before and after manipulation in nests of spotless starlings Sturnus unicolor breeding in nest boxes. Nest size was enlarged and elevated in a first group of nests by adding nest material to the base of the nest (enlarged nests); a second group of nests was elevated with a piece of plastic but without adding nest material (elevated nests); a third group of nests was not manipulated (control nests). Number of flies per nest increased significantly in enlarged and elevated nests compared to control nests. Moreover, distance to cavity entrance after manipulation was negatively associated with the increase in the number of flies per nest (i.e. nests closer to the entrance had more parasites). Thus, nest size, through its effect on distance between nest and cavity entrance, affected fly abundance. Cues produced by nest contents located closer to the cavity entrance may be detected more readily by ectoparasitic flies searching for hosts. These results suggest a novel constraint for the evolution of nest size in cavity‐nesting birds.